Penerapan Konseling Individu dengan Pendekatan Cognitive Behavioral Therapy untuk Menurunkan Kecemasan Berbicara Didepan Kelas Pada Siswa SMP Negeri 3 Luwuk - Anggitiadi, Anggitiadi; Endarwaty, Asrina; Wiesmayani, Wiesmayani (Universitas Syiah Kuala, 2025)
The purpose of this research is to determine the role of group counseling using CBT in reducing anxiety about speaking in front of the class among students of SMP Negeri 3 Luwuk. This research design is a quasi-experimental design with a non-equivalent control group design. A total of 62 students from grade VIII-B and VIII-C of SMP Negeri 3 Luwuk were the population. A sample of 16 students was selected using purposive sampling. Based on the research results on these 16 students, they were divided into two groups. The experimental group consisted of 8 students and the control group also consisted of 8 students. An Independent Test was conducted using SPSS 27 software to analyze the data. Based on the results of data analysis, there are 8 students in the experimental group and 8 students in the control group who experience a fairly high level of speaking anxiety. Then, the experimental group conducted group counseling for the 8 students and took post-tests for both the experimental and control groups. The research results showed that the average difference in anxiety for the experimental group was 88.5 in the high category and decreased to 72 in the low category.